Effect of Multimedia Teaching to the Achievement of Junior High School Students in Trigonometry - Zacal, Steve G. (JPAIR Institutional Research, 2014)
Modernization means advancement of technology. Since technology is now fast growing in any instance, it also affects student's behavior in their studies. This study was conducted to determine the effect of interactive multimedia instruction on the achievement of junior-high-school students in the subject Trigonometry. Design 10, the non-equivalent control-group format was used to conduct the experiment during the fourth quarter of school year 2010-2011. The section, third-year Mayon with 35 students made up the experimental group, while that of third-year Apo with 35 students became the control group comprising of 70 third-year students of Daniel R. Aguinaldo National High School as the subjects of the study. The experimental group was evaluated based on treatment X, which used the interactive multimedia instruction. The traditional method of teaching was used by control group and isolated from the experimental intervention and was evaluated during the pre-test and post-test periods. Data were retrieved using the test made by the investigator. It came out that both groups displayed learning improvement at the end of the study, but the magnitude of an increase significantly differed. The study concludes that interactive multimedia instruction led to higher improvement of teaching trigonometry than the conventional method adopted by the control group.
Keywords: Multimedia Instruction; academic achievement; non-equivalent control group design; Davao City; Philippines